A cell retention system composed of cellulose acetate hollow fiber membranes for cultivation of Dunaliella salina in a helical photobioreactor. Issue 7 (9th April 2019) - Ershad, Ghazaleh Amini; Jazini, Mohammadhadi; Fashandi, Hossein; Shariati, Mansour
Abstract: Background: One of the challenges in commercial‐scale cultivation of Dunaliella salina is low biomass productivity and concentration. In addition, cultivations in wastewaters may encounter some nutrient limitations. Hence, there is a need for a cultivation system which is capable of continuous provision of nutrients while the cells are retained in the system. In this study, the feasibility of using a cell retention system (CRS) for increasing biomass productivity and concentration of D. salina was investigated. The CRS was composed of cellulose acetate hollow fiber membranes (HFMs) coupled with a helical photobioreactor. Results: Using the produced HFMs with mean pore size of 124 nm and overall porosity of 78.9%, the rejection of D. salina microalgae was as high as 93.2%. Continuous cultivation of D. salina in the helical photobioreactor at a dilution rate of 0.48 day −1 resulted in a biomass productivity (concentration) of 4.9 × 10 7 cells L −1  h −1 (2.7 × 10 6 cells mL −1 ). Interestingly, cultivation at the same initial dilution rate (0.48 day −1 ) in the helical photobioreactor coupled with the CRS resulted in a biomass productivity (concentration) of 9.3 × 10 7 cells L −1  h −1 (6.7 × 10 6 cells mL −1 ). Conclusions: The results revealed the potential of the proposed system for enhancing biomass productivity by 90% and biomass concentration by more than twofold. The cultivation system is also proposed as a potential tool for cultivations in wastewaters. © 2019 Society of Chemical Industry